PENGARUH BRAND IMAGE DAN PERSEPSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI PT INDOMARCO PRISMATAMA (INDOMARCO) (Studi Kasus Pada Mahasiswa Semester VIII (Delapan) Program S1 Manajemen STIE Sultan Agung Pematangsiantar) - Desiana, Lusy; Lie, Darwin; Efendi, Efendi; Sherly, Sherly (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2018)
The purpose of this study are: 1. To determine the image of brand image, consumer perception, and purchasing decisions in Indomaret. 2. To determine the influence of brand image and consumer perception of purchasing decision in PT Indomarco Prismatama (Indomaret) either simultaneously or partially. This research was done by using design of literature and field research. The type of data used in this research is qualitative and quantitative data. Sources of data are primary and secondary data. The population used in this reseaarch were students of STIE Sultan Agung Pematangsiantar Semester VIII T.A. 2016/2017 and the sample used of 89 respondents. Data was collected by questionary, interview and documentation. The technique of analyzing is multiple linear regression, coefficient correlation, coefficient determination and hypothesis testing by F test and t test. The result of this study can be summarized as follows: 1. Indomaret brand image is good, Indomaret consumer perceptions have been good and consumers have agreed with the purchase decisoin made. 2. The results of regression analysis is Ã = 9,952 + 0,558X1 + 0,280X2, its means that brand image and consumer perceptions had a positive effect on purchasing decisions. 3. The results of the analysis correlations get value r = 0,855, it means that there is high and positive relationship between brand image, consumer perceptions to the purchasing decisions. And the cefficient of determination obtained value R Square = 0,730, it means that consumer purchasing decisions can be explained by the brand image and consumer perceptions of 73%. 4. The results of testing the hypothesis H0 is rejected, its means that brand image and consumer perceptions had a positive and significant effect to the purchasing decisions in PT Indomarco Prismatama (Indomaret) either simultaneously or partially. The suggestion of this research is to improve the brand image, to improve the brand image new innovations that make consumers comfortable shopping. To improve consumer perceptions should Indomaret pay attention to ceptetitors and always check the stock of goods inthe warehouse. While for purchasing decisions, need to improve new things like providing free wifi, ready-brewed coffee, and comfortable seating so that consumers feel comfortable shopping in PT Indomarco Prismatama (Indomaret). Keywords: Brand Image, Consumers Perceptions,and Purchasing Decisions